On “gardens” and “cars”: Otto Jespersen’s metaphors for Interlinguistics and his quest for the best language - Fortes, Fabio (Investigationes Linguisticae, 2023)
With this paper, I intend to present some theoretical contributions that Jespersen made to the field of Interlinguistics, by analysing some images he used for understanding the field of Interlinguistics and the character of interlanguages, based on his articles published from 1921 to 1933: “Artificial languages ​​after the World War” (AL 1921), “History of our language” (HL 1921); “Introduction, an international language” (IL 1928), “Interlinguistics” (I 1931) and “Nature and art in language” (NA 1933). I assume here a broad definition of Interlinguistics, as the interdisciplinary branch of linguistic knowledge dealing with international communication by means of interlanguages, which can be both ethnic languages used as a common ground for speakers of different mother tongues, and created languages, such as Esperanto, designed for international and intercultural communication. I approach particularly the concepts and terminology proposed by Jespersen to refer to these interlanguages and the parameters and norms for the construction, standardization and adoption of a planned language for international communication. I do not intend to present a general overview of Jespersen’s contributions to Theoretical Linguistics or to English Language Studies.